The Effect of Curcumin Administration on p53 and Caspase-3 Expression in Cervical Cancer HeLa Cell Culture - Purba, Irene Silvia; Irwanto, Yahya; Rahardjo, Bambang; Handayani, Puspita (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2024)
Introduction: Cervical cancer is a type of cancer with 605,000 new cases globally each year, with a mortality rate of 340,000. Curcuma longa, or curcumin, has the potential to enhance apoptosis in cervical cancer cells through the NF-kB-p53-caspase-3 pathway. Material and Methods: This in vitro experimental study employed a Completely Randomized Design (CRD) using HeLa cell cultures derived from cervical adenocarcinoma (ATCC® CCL2™). Cells were grown in Dulbecco's Modified Eagle Medium (DMEM) and treated with curcumin at concentrations of 25 µg/mL, 50 µg/mL, 100 µg/mL, 150 µg/mL, and 250 µg/mL. Cytotoxicity was assessed using the CCK-8 assay, apoptosis via flow cytometry, and p53 and caspase-3 expression using immunofluorescence. Statistical analysis was performed with IBM Statistics SPSS 25. Results: There was an increase in the percentage of apoptosis, p53 expression, and caspase-3 expression. At a dose of 100 µg/mL, total apoptosis increased significantly, reaching nearly 25% (p=0.000). P53 expression significantly increased at curcumin doses of 50 µg/mL and 100 µg/mL (p=0.021). There was a significant increase in caspase-3 expression, reaching approximately 86.2%, with a maximum effect at a dose of 100 µg/mL (p=0.002). Conclusion: Curcumin shows promising potential as an anticancer agent by reducing cell viability and enhancing apoptotic activity in HeLa cervical cancer cells.